Influence of the amount of intermetallics on the degradation of Mg-Nd alloys under physiological conditions. (February 2021) - Zhang, Yaping; Huang, Yuanding; Feyerabend, Frank; Blawert, Carsten; Gan, Weimin; Maawad, Emad; You, Sihang; Gavras, Sarkis; Scharnagl, Nico; Bode, Julia; Vogt, Carla; Zander, Daniela; et al.
Abstract: The influence of amount of intermetallics on the degradation of as-extruded Mg-Nd alloys with different contents of Nd was investigated via immersion testing in DMEM+10% FBS under cell culture conditions and subsequent microstructural characterizations. It is found that the presence of intermetallic particles Mg41 Nd5 affects the corrosion of Mg-Nd alloys in two conflicting ways. One is their negative role that their existence enhances the micro-galvanic corrosion. Another is their positive role. Their existence favours the formation of a continuous and compact corrosion layer. At the early stage of immersion, their negative role predominated. The degradation rate of Mg-Nd alloys monotonously increases with increasing the amount of intermetallics. Mg-5Nd alloy with maximum amount of intermetallics suffered from the most severe corrosion. With the immersion proceeding (≥7 days), then the positive role of these intermetallic particles Mg41 Nd5 could not be neglected. Owing to the interaction between their positive and negative roles, at the later stage of immersion the corrosion rate of Mg-Nd alloys first increases with increasing the content of Nd, then reaches to the maximum at 2 wt. % Nd. With a further increase of Nd content, a decrease in corrosion rate occurs. The main corrosion products on the surfaces of Mg-Nd alloys include carbonates, calcium-phosphate, neodymium oxide and/or neodymium hydroxide. They are amorphous at the early stage of immersion. With the immersion proceeding, they are transformed to crystalline. The existence of undegradable Mg41 Nd5 particles in the corrosion layer can enhance the crystallization of such amorphous corrosion products. Graphical abstract: Image, graphical abstract